PHYSICAL EDUCATION TEACHERS AND THEIR ROLE IN ENHANCING LEADERSHIP SKILLS AMONG MIDDLE SCHOOL STUDENTS IN MAYSAN GOVERNORATE - Dr. Muhammad Malik Salim (American Journals, 2023)
This research deals with an important topic in the teaching and educational process in Iraq, which is leadership and its skills. The research aims to identify the role of the teacher of physical education in enhancing leadership skills among middle school students in the city of Amarah, the center of Maysan Governorate, from the teachers' point of view. The research community consisted of (93) The research sample consisted of (80) teachers of physical education for the preparatory stage. The researcher used the descriptive survey method to suit the nature of the research, and a questionnaire was prepared to measure the leadership skills of middle school students, and its validity and stability were confirmed, and the results showed that the role of the physical education teacher was high in enhancing the leadership skills of students, as the results showed There are statistically significant differences among middle school students, and the results showed that there are no statistically significant differences for the educational unit in the governorate in general. The researcher reached a set of results, from which he came out with several recommendations, including the need to hold workshops and training courses for teachers to enhance leadership skills and spread leadership awareness among students to prepare a conscious generation with leadership qualities and skills aimed at benefiting society in general.
Keywords: Physical education teacher, leadership skills, middle school.